Neither God nor others: a qualitative study of strategies for avoiding suicide among homeless people - Testoni,Ines (2020)
Abstract Introduction Drug addiction and alcoholism characterize the existential condition of most homeless people, while the risk of suicide runs in parallel. Objectives Following the Provisional Model (PM), this study aimed to explore the relationships between addiction, suicidal ideation, and religiosity among 13 homeless people, and the roles of bonding ties (within the group) and bridging ties (intergroup). Method The study is rooted in the field of qualitative psychology research. A survey was conducted, analyzing the personal accounts of participants and applying the PM psychological interpretation integrated with theory from literature on drug addiction, religiosity, and suicidal ideation in the field of homelessness. Results Outcomes show that suicidal ideation appears in the first phase of homelessness and is opposed by alcoholism and drug addiction. Religiosity does not help to counteract suicidal ideation or to create bonding relationships. Conversely, drugs and alcohol seem to be more useful for preventing suicide, but also do not help in bonding relationships. Conclusion Our survey only partially confirmed the PM, because the main result was the importance of relationships between suicidal ideation and alcohol/drug abuse during the initial phase of becoming homeless, while the importance of bonding ties deriving from addiction behavior did not emerge.